Neurotropic influenza A virus infection causes prion protein misfolding into infectious prions in neuroblastoma cells - Hideyuki Hara (Nature Portfolio, 2021)
Abstract Misfolding of the cellular prion protein, PrPC, into the amyloidogenic isoform, PrPSc, which forms infectious protein aggregates, the so-called prions, is a key pathogenic event in prion diseases. No pathogens other than prions have been identified to induce misfolding of PrPC into PrPSc and propagate infectious prions in infected cells. Here, we found that infection with a neurotropic influenza A virus strain (IAV/WSN) caused misfolding of PrPC into PrPSc and generated infectious prions in mouse neuroblastoma cells through a hit-and-run mechanism. The structural and biochemical characteristics of IAV/WSN-induced PrPSc were different from those of RML and 22L laboratory prions-evoked PrPSc, and the pathogenicity of IAV/WSN-induced prions were also different from that of RML and 22L prions, suggesting IAV/WSN-specific formation of PrPSc and infectious prions. Our current results may open a new avenue for the role of viral infection in misfolding of PrPC into PrPSc and formation of infectious prions.